Smoking and serological response to influenza vaccine - Won Suk Choi; Mary Patricia Nowalk; Krissy Moehling Geffel; Michael Susick; Sean Saul; Chyongchiou Jeng Lin; Ted M. Ross; Richard K. Zimmerman (Human Vaccines & Immunotherapeutics)
Cigarette smoking confers additional risk from influenza. This study assessed the effect of smoking on humoral immune response to influenza vaccine. Adults ≥50 y of age were enrolled during the 2011–2016 influenza vaccination seasons in an observational prospective study. Non-fasting whole blood samples for hemagglutination inhibition (HAI) assays were obtained from participants at pre- and 28 d post-clinically administered, trivalent influenza vaccination. Among 273 participants, 133 subjects self-reported as never smokers, 87 as ex-smokers, and 53 as current smokers. Postvaccination geometric mean HAI titers were significantly higher among smokers for A/H1N1 (p = .031) and A/H3N2 (p = .001). Relative to never smokers, smoking was independently related to seroconversion to A/H1N1, A/H3N2 and B. The adjusted odd ratios (ORs) were 5.2 [95% confidence interval (CI), 2.3, 11.5] for seroconversion to A/H1N1, 5.4 (95% CI, 2.4, 12.1) for A/H3N2, and 2.7 (95% CI, 1.3, 5.7) for B. Smoking was also independently related to seroprotection to A/H1N1, A/H3N2 and B. The ORs were 3.6 (95% CI, 1.6, 8.08) for seroprotection to A/H1N1 in smokers, 2.7 (95% CI, 1.14, 6.5) for A/H3N2, and 2.5 (95% CI, 1.1, 5.7) for B. Although the mechanism is unclear, smokers showed a better immune response to influenza vaccination than never smokers and ex-smokers. The results can be used to emphasize the value of influenza vaccination for smokers.